Determination of total phenol derivatives obtained from lignin black liquor as alternative to production (Publicaciones en Ciencias y Tecnología, 2018)
Lignin is an industrial waste being worthless in papermaking byproduct of black liquor obtained from the pulping process in some Venezuelan plants. The black liquor is obtained from the Kraft pulping process to extract lignin sulphite by acid precipitation and quantify the amount of total phenols in such lignin products used in this study. Spectrophotometry Molecular absorption in the UV-Visible and Infrared Spectroscopy (FTIR) region were used to carry out these study techniques. The products obtained in the study had the same signs than commercial lignin (LA), along with the extracted lignin present little degradation HCl, confirmed by infrared spectra. Also, the amount of total phenols was quantified in derivative lignin obtained using the Folin-Ciocalteu. In the sulphite process extracted lignin with acetic acid derivative contains more phenols, and in the Kraft process, the derivative lignin extracted with fewer nitric acid present. The amount of total phenolics present in these derivatives are good for making antiseptics, detergents, nylon, resin and many industrial products., , , ,Lignin, waste, precipitation, phenols, antioxidants
Keywords: Lignin; waste; precipitation; phenols; antioxidants